Types of Conflict and Conflict Management Strategies Found In “Mile 22” Movie - I Kadek Arisetiawan; I G.A. Sri Rwa Jayantini; I.B. Gde Nova Winarta (Austronesian: Journal of Language Science & Literature, 2024)
The presence of diverse conflicts in literature determines the good and bad of a movie. A good plot is also influenced by how movie-makers plan wonderful resolves within the conflicts. This study aims to discover types of conflicts and conflict management strategies found in Mile 22 movie. This study uses descriptive qualitative method to gather and analyse the data. The data are taken from the “Mile 22” movie, supported by a full transcript of the movie gathered from the Subslikescript website (2018). When collecting the data, the researchers used observation and note-taking techniques to gather the data. The theory of Kenney (1996) and Thomas and Kilmann (2008) are used as the theoretical framework for this paper. The finding showed that from sixteen data, there are two internal conflicts and 14 external conflicts, which divided into eleven man against man conflict, and two man against society conflicts. All strategies were found used to resolve the conflicts faced by the main characters, where competitive were found in six data, collaborative in one data, compromising in three data, accommodating in four data, and avoiding in two data.